(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article discusses the use of artificial intelligence to optimize the management of e commerce in the digitalization of the economy. AI-based management decision support methods and mathematical rules for knowledge base are proposed. Also considered is the evaluation of the effectiveness of managerial decisions and forecasts for increasing the government efficiency index, which requires improving the regulatory framework and cybersecurity.